Influence of Information Flow on Logistics Management in the Industry 4.0 Era - Ayodeji Adeitan; Clinton Aigbavboa; Olufemi Bamisaye (International Journal of Supply and Operations Management, 2021)
Industry 4.0 technologies have capacities to improve competitiveness in the logistics chain by taking advantage of information flow through the logistics processes. This paper aims to determine the influence of effective and new information flow on logistics management in Nigeria. The methodology used in this study includes; the quantitative methodology, a mean item score, exploratory factor analysis, normality test, and Man-Whitney test. Findings revealed negotiating better contracts, better product tracking, better quality logistics information flow, expanded network, and enhanced information transfer as the top five effect of information flow on logistics management in Nigeria. It is recommended that Nigerian companies engaging in logistics activities need to adopt industry 4.0 technologies to aid effective and new information flow in their logistics management processes. Finally, the growth of logistics firm and its ability to compete depend on effective information flow.